Fueling Productivity: Exploring the Impact of Work Motivation, Work Environment, Work Commitment, and Competence on Teaching Staff's Performance - Surahman, Arief (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
Many educational institutions realize that the success or failure of an educational institution by increasing the productivity and efficiency of the institution does not only depend on supporting equipment, adequate infrastructure. This study aims to determine the influence of work motivation, work environment, work commitment and competence on employee productivity, sampling method with saturated sample method. In this study the population amounted to 146 people, and the sample was randomly selected, the sample in this study was 107 people. The results of the Competency variable have a calculation of 2.694 < ttable 1.984, where the significance value is 0.389 > 0.008, so it can be concluded that simultaneously the Adjusted R Square value of Work Motivation, Work Environment, Work Commitment and Competency together affects 36.9% on the Employee Productivity variable, while the remaining 63.1% is influenced by other variables, which are not contained in this study.